2020
DOI: 10.1155/2020/3178214
|View full text |Cite
|
Sign up to set email alerts
|

Butterbur (Petasites hybridus) Extract Ameliorates Hepatic Damage Induced by Ovalbumin in Mice

Abstract: The liver is the most vital organ that could be influenced by inducers of hypersensitivity such as ovalbumin. The current study was carried out to explore the effects of butterbur (Petasites hybridus) extract on the ovalbumin-induced liver hypersensitivity in Swiss albino male mice. Animals were divided into 4 groups, 1st group served as a control group, 2nd group treated with daily oral administration of 75 mg/kg of butterbur extract, 3rd group received single oral dose 100 mg/kg of ovalbumin to induce hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This anaphylaxis was manifested by the high levels of MDA and NO, and the remarkable decrease in SOD activity and GHS levels in the liver ( Figure 4 ). These changes in the hepatic oxidative indices were in agreement with those in the OVA-induced liver hypersensitivity reported before [ 36 ]. Polyphenol possesses a wide range of antioxidant activities.…”
Section: Discussionsupporting
confidence: 92%
“…This anaphylaxis was manifested by the high levels of MDA and NO, and the remarkable decrease in SOD activity and GHS levels in the liver ( Figure 4 ). These changes in the hepatic oxidative indices were in agreement with those in the OVA-induced liver hypersensitivity reported before [ 36 ]. Polyphenol possesses a wide range of antioxidant activities.…”
Section: Discussionsupporting
confidence: 92%
“…TdT is expressed in certain immune cells and acts during V(D)J recombination -the process that generates antibody diversity. ABC detection kits depend on the affinity of avidin (or streptavidin) for biotin (Alhusayan et al, 2020). The endpoint of apoptosis which is indicative of positive staining can be represented by a dark brown signal.…”
Section: Methodsmentioning
confidence: 99%
“…Undoubtedly, butterbur is a rich source of antioxidants, and a recent study demonstrated butterbur extract powder of Petasites hybridus to ameliorate liver injury in ovalbumin-induced liver hypersensitivity reactions in Swiss albino male mice. Indeed, butterbur significantly decreased liver enzymes and oxidative stress and reduced the expression of markers for inflammation and fibrosis of liver tissues as shown by histopathology ( 54 ). Another recent report highlights the antioxidant activity of Petasites japonicus maxim.…”
Section: Butterbur's Composition and Therapeutic Benefitsmentioning
confidence: 98%